Examining War Takjil as a Practice of Social Cohesion: Interfaith Interaction on Social Media - Fathoni, Fuad Hizbillah; Wahidi, M. Irsyad (Contemporary Society and Politics Journal, 2025)
This study explores the phenomenon of the war takjil on TikTok during Ramadan 2024 as a manifestation of interreligious social cohesion in Indonesia. Emerging amidst heightened political tensions and religious identity polarization in the lead-up to the general election, this phenomenon stands in contrast to the dominant narratives of conflict often found on social media. The war takjil trend instead showcases harmonious interactions between Muslim and non-Muslim communities in the shared social activity of seeking takjil (pre-fast breaking meals). Employing a qualitative approach through netnographic methods, the study draws on Émile Durkheim’s theory of social cohesion to analyze the organic solidarity cultivated within digital spaces. The findings reveal that the war takjil reflects a shift from a condition of anomie toward social harmony, and highlights the role of social media, particularly TikTok, as a new arena for fostering solidarity and cross-identity communication. Thus, this phenomenon offers a concrete example of how religious and cultural practices can intertwine to form inclusive and constructive social cohesion in the digital age.